Metabolism Disrupting Chemicals and Alteration of Neuroendocrine Circuits Controlling Food Intake and Energy Metabolism - Marraudino, Marilena; Bonaldo, Brigitta; Farinetti, Alice; Panzica, GianCarlo; Ponti, Giovanna; Gotti, Stefano (Frontiers in Endocrinology, 2019)
The metabolism-disrupting chemicals (MDCs) are molecules (largely belonging to the category of endocrine disrupting chemicals, EDCs) that can cause important diseases as the metabolic syndrome, obesity, Type 2 Diabetes Mellitus or fatty liver. MDCs act on fat tissue and liver, may regulate gut functions (influencing absorption), but they may also alter the hypothalamic peptidergic circuits that control food intake and energy metabolism. These circuits are normally regulated by several factors, including estrogens, therefore those EDCs that are able to bind estrogen receptors may promote metabolic changes through their action on the same hypothalamic circuits. Here, we discuss data showing how the exposure to some MDCs can alter the expression of neuropeptides within the hypothalamic circuits involved in food intake and energy metabolism. In particular, in this review we have described the effects at hypothalamic level of three known EDCs: Genistein, an isoflavone (phytoestrogen) abundant in soy-based food (a possible new not-synthetic MDC), Bisphenol A (compound involved in the manufacturing of many consumer plastic products), and Tributyltin chloride (one of the most dangerous and toxic endocrine disruptor, used in antifouling paint for boats).